SOME IMPLEMENTATION PROBLEMS INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Sizov, V.V. (Pedagogy of Higher and Secondary Education, 2006)
This article is devoted to the basical organizational problems of for mulation electronic information trends in educational process.